"The Holocaust" or "The Salvation of Democracy": Memory and Political Struggle in the Aftermath of Colombia's Palace of Justice Massacre. (May 2015) - Leal-Guerrero, Sigifredo
The massacre known as the Palace of Justice Holocaust is an important object of public concern in Colombia. After 29 years, social agents struggle in fields such as public activism, legal claims, and artistic creation to construct and legitimate accounts of what happened and inscribe them in collective memory as "the truth." An analysis of these struggles, developed from inside and outside the state and from diverse points of the political spectrum, makes it possible to identify the meaning frames in which the people taking part in these struggles construct narratives of the massacre, such as the Jewish-Christian tradition, discourses on human rights and the memory of the Shoah, national security doctrines, and Nazi anticommunist anti-Semitism. La masacre conocida como el Holocausto del Palacio de Justicia es un importante objeto de interés público en Colombia. Después de 29 años de acontecida, diversos actores sociales continúan luchando en campos como el activismo político, los reclamos legales y la creación artística para construir y legitimar versiones sobre lo sucedido, e inscribirlas en la memoria colectiva como "la verdad". Un análisis de esas luchas, desarrolladas desde dentro y fuera del Estado y desde diversos puntos del espectro político, permite identificar los marcos de sentido dentro de los cuales dichos actores construyen narrativas sobre la masacre. Algunos de esos marcos son la tradición judeo-cristiana, los discursos sobre los derechos humanos y la memoria de la Shoá, las doctrinas de seguridad nacional y el antisemitismo anticomunista nazi.